Analysis of the mannose 6 phosphate reductase gene expression. In coffee trees submitted to water deficit - Freire, Luciana Pereira; Marraccini, Pierre Roger; Rodrigues, Gustavo Costa; Andrade, Alan Carvalho (Coffee Science - ISSN 1984-3909, 2013)
The effects of water deficit on the gene CaM6PR expression, encoding mannose -6- phosphate reductase, were evaluated in coffee trees in the formation phase of coffee cultivars IAPAR59 ( Villa Sarchi x Timor hybrid HT832 / 2) and RUBI MG 1192 (Mundo Novo x Catuaí ) of Coffea arabica, respectively regarded as tolerant and sensitive to water stress. The cultivars were planted in December 2007 in the experimental field of Embrapa Cerrados - DF ( CPAC ) and culturedfor two years (2008 and 2009 ) with (I) and without ( NI ) irrigation. For each year two assessments were carried out (P1, not stressed, during the rainy season and P2 , dry season ). For both cultivars, the CaM6PR gene expression measured inleaves through quantitative PCR, showed a strong increase in the dry season for non-irrigated plants when compared with irrigated plants. In addition, the expression of this gene was always greater in IAPAR59 than in RUBI MG 1192. Also, therewas an increased expression of this gene in 2008 when compared to 2009. This difference could be a direct consequence of drought stress levels received by plants, since drought conditions in 2008 were more severe than in 2009. Thus, in this work, we propose the use of the CaM6PR gene as a molecular marker to evaluate the stress level of the coffee plants submitted to water deficit.